Addressing AMR and planetary health in primary care: the potential of general practitioners as change agents - Paula Tigges; Alexandra Greser; Ildikó Gágyor; Judith Kraft; Andy Maun; Guido Schmiemann; Eva-Maria Schwie; Eva-Maria Schwie; Christoph Heintze; Angela Schuster (Frontiers Media S.A., 2024)
IntroductionAntimicrobial resistance is closely linked with the health and stability of environmental systems and therefore a challenge for the health of the planet. General Practitioners, owing to their trusted positions and close patient relationships, can play a crucial role in addressing antimicrobial resistance within the framework of Planetary Health. The goal of our study was to examine General Practitioners' knowledge, attitude, and practice regarding the linkage of antimicrobial resistance with Planetary Health to understand their potential as agents of change in this domain.Materials and methodsWe conducted 19 guided interviews with General Practitioners from four different German federal states (August-September 2022). Participants were selected from the intervention group of the RedAres randomized controlled trial, a study designed to optimize therapy and prescribing practices for uncomplicated urinary tract infections in general practice. Data were analyzed using Mayring's structured qualitative content analysis and the typology approach by Kelle and Kluge.ResultsGeneral Practitioners generally demonstrated the ability to identify the interlinkages between antimicrobial resistance and Planetary Health. However, they exhibited varying levels of knowledge, problem awareness, and accountability for the associated challenges and partially outsourced the responsibility for Planetary Health. Some General Practitioners were capable of integrating Planetary Health arguments into patient counseling. They recognized rational prescribing practice, self-reflection on antimicrobial resistance and Planetary Health, interprofessional exchange, and raising awareness among patients as potential avenues for engagement in promoting Planetary Health.DiscussionAs antimicrobial resistance is increasingly recognized as a Planetary Health challenge, empowering General Practitioners as change agents requires tailored measures based on their level of previous knowledge and their attitude toward Planetary Health. General Practitioners express a need for concrete advice on how to integrate antimicrobial resistance as a Planetary Health topic into their daily activities. Developing and evaluating adaptable training materials is essential. Additionally, the integration of Planetary Health outcomes into clinical guidelines could accelerate the adoption of this dimension in antibiotic prescribing practices within primary care settings.